The efect of visual merchandising on consumer buying behavior in Pantai Timur Hypermarket - Lim, Sen Siang; Mustaffa, Muhammad Fakhrul Amin; Mesman, Nur Azratul Azrahana; Jamaludin, Zubaidah (2015)
Retail industry in Malaysia quite booming and we can see diversity of type of business which they already establish in market. There is fierce competition occur within various retailer or marketer in visual merchandising term. The study is aimed to discover the impact of visual merchandising elements on customer buying behavior of the customer visiting Pantai Timur Hypermarket, Pengkalan Chepa, Kelantan. Four main visual merchandising elements are window display, mannequin display, promotional signage and floor merchandising highlighted in this study. These element were studied and its impact on customer buying behavior is found out. The result shown that all elements were had positive relationship towards customer buying behavior. Hence, visual merchandising is vital for strategic marketing decision in term of company performance regarding to the sales and to ensure the business running effectively